RADON MEASUREMENTS IN BIG BUILDINGS: PILOT STUDY IN RUSSIA. Issue 2 (31st October 2020) - Vasilyev, A; Yarmoshenko, I; Onishchenko, A; Hoffmann, M; Malinovsky, G; Marenny, A; Karl, L
Abstract: Detailed analysis of indoor radon concentration distribution by floors was conducted in four children institutions, one office building and two residential houses in Russian cities to develop approaches to draw up a program of radon survey for big buildings. Higher variability of radon concentration was found in high geogenic radon potential (GRP) area when the soil is the main source of radon. No essential dependence of radon concentration on the floor in high-rise buildings was found in low GRP area. The number of required radon measurements is estimated using obtained characteristics of radon variability.